MANAJEMEN KONFLIK ANTARBUDAYA PADA ORGANISASI INTERNASIONAL - Dwi Hapsari W, Ellysabeth Ratih (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
ABSTRACTCommunicating effectively with people from different cultures in the workplace is very challenging. Barriers to intercultural communication can occur, such as anxiety, roles and norms, beliefs and values, stereotypes and ethnocentrism. These barriers can cause internal conflict within a group of organizations or companies that have employees with different cultures. Internal conflicts that occur will also prevent the organization to achieve its goals. The current issue is how the management of intercultural communication conflicts occurs in international organizations. The purpose of this study is to describe the experience of employees of international organizations in the management of intercultural communication conflicts by knowing the negotiation of employee identity, knowing the types and forms of conflict experienced by employees of international organizations and knowing the form of face management in inter-cultural communication conflict management at employees of international organizations. The subject of this research are international organization employees from India, UK, Indonesia and China. Theory used in this study are Identity Negotiation Theory, Face Negotiation Theory, Effective Intercultural Workgroup in Communication Theory and Thomas and Killman’s Conflict Management Model. The results showed that the negotiation of identity between collectivist and individualist cultures that occurred begins with the interaction between cultures in the form of communication behavior, language, personal character and response from other employees. Differences in ways of thinking and view are the main causes of conflict between individualist and collectivist cultures. Face owned by each culture influences other differences such as how individuals perceive themselves in conflict, self-priority in conflict, and the conflict management style used. Intercultural conflict management that occurs requires a third party as a mediator.Keywords : Intercultural Communication, Conflict Management, International Organization